2009
DOI: 10.1111/j.1399-6576.2008.01895.x
|View full text |Cite
|
Sign up to set email alerts
|

Day surgery in Finland: a prospective cohort study of 14 day‐surgery units

Abstract: Along with the growing demand for day surgery, Finnish public hospitals have succeeded in providing good-quality care, and there still seems to be potential to increase the share of day surgery. Easily accessible benchmarking tools are needed for quality control and learning from peers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 16 publications
3
29
0
2
Order By: Relevance
“…18 Day surgery is an innovative treatment whose popularity and demand is growing all the time. 1,6,19,20 It offers high-quality and effective surgical management for a wide range of procedures 6,18,20 and is a well-designed, cost-effective and people-serving activity. 6,7,18,19 Surgery and pain treatments constantly develop, so more and more surgeries can be done as a day surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Day surgery is an innovative treatment whose popularity and demand is growing all the time. 1,6,19,20 It offers high-quality and effective surgical management for a wide range of procedures 6,18,20 and is a well-designed, cost-effective and people-serving activity. 6,7,18,19 Surgery and pain treatments constantly develop, so more and more surgeries can be done as a day surgery.…”
Section: Introductionmentioning
confidence: 99%
“…6 In Finland, about 50% of elective operative surgery is done as day surgery, 6 with patients being very satisfied with day surgery. 7,20,24,25 While the health care system benefits from the lower costs of day surgery, patients appreciate a rapid recovery and effective analgesia. 18 Day surgery patients arrive at the hospital on the day of surgery and leave home on the same day 22 or at the latest within 24 hours of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled pain is also a major cause of nausea and vomiting, further extending the patient's stay in the recovery room (Eriksson et al, 1996;Michaloliakou et al, 1996). The most common reason for unplanned hospital admission across 14 day-surgery units in Finland was unrelieved pain (Mattila & Hynynen, 2009 Level III-2).…”
Section: Adverse Effects Of Painmentioning
confidence: 99%
“…Those outcomes were lower than seen in other studies of ambulatory surgery overall [14][15][16][17]. In this respect, the data provided by Matilla et al [18], after a thorough study of day surgery of all specialties in Finland, revealed rates of admission of 5.9 % and readmission within 24 h postoperatively of 0.1 %. As such, our study may provide a benchmark to evaluate future outpatient orthopedic surgery disposition rates.…”
Section: Discussionmentioning
confidence: 72%